Hubungan Self Care dengan Kualitas Hidup Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Bungi di Kota Baubau - Taswin Taswin; Rahi Mustika Ayu Nuhu; Eky Endriana Amirudin; Muhammad Subhan (HB PRESS, 2022)
Diabetes Mellitus (DM) is a health problem characterized by an increase in blood sugar levels that cannot be cured and can only be controlled so that it requires self-care. This study aimed to determine the relationship of self-care in terms of monitoring diet and compliance with taking medication with the quality of life of diabetes mellitus patients in the working area of ​​Puskesmas Bungi. This type of research is a quantitative study with a cross sectional study design. The study population were 291 people. A total of 168 samples were selected using probability sampling. Collecting data through primary data, namely questionnaires and secondary data. The data analysis used was univariate and bivariate analysis with the chi square test. The results showed the relationship of monitoring diet (diet) with the quality of life of patients with diabetes mellitus showed p value = 0,000 or p value <0,05, which means there is a relationship between monitoring diet (diet) and quality of life of patients with diabetes mellitus, the correlation between medication adherence and quality of life of patients with diabetes mellitus showed p value = 0,830 or p value> 0,05, which means that there was no relationship between medication adherence and quality of life for patients with diabetes mellitus. Based on these results diabetes mellitus patients are expected to continue to improve self-care behavior to obtain health status and achieve a better quality of life and prevent further disease complications.